Synthesis of NiMoS4 for High-Performance Hybrid Supercapacitors. Issue 12 (21st September 2017) - Du, Dongwei; Lan, Rong; Humphreys, John; Xu, Wei; Xie, Kui; Wang, Huanting; Tao, Shanwen
Abstract : Transition metal sulfides have been suggested as promising materials for efficient energy storage with superior electrochemical performances. Compound NiMoS4 -A was synthesized by a facile chemical co-precipitation process, followed by calcining at 450°C in Ar. The as-prepared NiMoS4 -A electrode exhibits a high specific capacity of 313 C g −1 at 1 A g −1 and good rate capability (83% retention at 10 A g −1 ). Electrochemical impedance spectroscopy (EIS) results indicate that the good performances could be attributed to the low internal and charge transfer resistances. Additionally, the quantitative charge storage analysis reveals that the faradaic redox process dominates at lower scan rates (78% at 1 mV s −1 ), while the capacitive effect dominates at higher scan rates (56% at 20 mV s −1 ). Furthermore, a hybrid supercapacitor (HSC), with NiMoS4 -A as the positive electrode and activated carbon (AC) as the negative electrode, displays a high energy density of 35 Wh kg −1 at an average power density of 400 W kg −1 . Meanwhile, the HSC exhibits excellent cycle stability, maintaining 82% of the initial capacitance after 10000 charge-discharge cycles even at a high current density of 5 A g −1 . These good electrochemical performances indicate that NiMoS4 -A is a promising positive electrode material for hybrid supercapacitors.